RELATING TEACHER’S ORAL CORRECTIVE FEEDBACK TO YOUNG LEARNERS’ UPTAKE: A CASE STUDY IN A YOUNG LEARNER EFL CLASSROOM - Elis Homsini Maolida (University of Kuningan, 2017)
This study explores various types of oral corrective feedback in relation to learners’ uptake in a young learner EFL classroom in Indonesia. It employed a qualitative research design embracing the characteristics of a case study. The data were mainly collected from 540 minutes video recording and observation to capture types of teacher’s oral corrective feedback and learners’ uptake in the classroom interaction. Teacher’s lesson plans were also analyzed to look at possible contribution on teacher’s choice of corrective feedback and learners’ uptake. The first finding reveals that the teacher employed seven types of oral corrective feedback; recast, elicitation, clarification request, explicit correction, repetition, metalinguistic feedback, and paralinguistic signal. As result, the students responded by various types of uptake such as repair and need repair. The distribution of learners’ uptake following different types of oral corrective feedback shows that output prompting feedback strategies tend to be more successful in encouraging learners’ uptake than input provided by feedback strategies. It is also noteworthy that elicitation and repetition led to be the highest number of repair. The fact that input providing feedback strategies result in fewer uptakes, however, tends to be resulted from the teacher’s choice to continue the topic in a certain context which shows the influence of learning contexts and teacher’s objectives on the choice of teacher’s corrective feedback and the occurrence of uptake.Keywords: oral corrective feedback, learners’ uptake, young learner